EXOME SEQUENCING AND THE DIAGNOSTICS OF COMPLEX DISEASE PREDISPOSITION IN PREVENTIVE MEDICINE - N. V. Shcherbakova (Кардиоваскулярная терапия и профилактика, 2013)
The further development of preventive medicine in the 21st century may be impossible without the assessment of individual patients’ genetic data. At present, genetic methods are the gold standard in the diagnostics of monogenic diseases. Recently, genetic factors linked to complex (multifactorial) diseases, such as coronary heart disease and arterial hypertension, have been actively explored. This review focuses on the possible identification of new genetic factors of complex disease heritability, using the exome sequencing approach.